Partnership Patterns and Production Factors in Rice Farming (Case Study: PT Ortani Mitra Sejahtera in Ponorogo Regency) - Jesika Ayu Nur Islami; Nuriah Yuliati; Ida Syamsu Roidah (Department of Tadris IPS FITK UIN Siber Syekh Nurjati Cirebon, 2024)
Ponorogo Regency is one of the rice centers in East Java. However, farmers in Ponorogo Regency face challenges regarding limited capital for their agricultural activities and difficulties in obtaining fertilizers. PT Ortani Mitra Sejahtera is a company that partners with farmers in Ponorogo Regency to provide the necessary facilities. Therefore, this study aims to analyze (1) the partnership pattern between PT Ortani Mitra Sejahtera and partner farmers in Ponorogo Regency and (2) the factors influencing the production of partner rice farming. This research was conducted at PT Ortani Mitra Sejahtera in Ponorogo Regency from December 2023 to March 2024. This study used a mixed-method research design. A sample of 33 respondents was determined using purposive sampling method. Data analysis was performed using Maximum Likelihood Estimator (MLE) with frontier 4.1c software. The results showed that the partnership pattern between PT Ortani Mitra Sejahtera and farmers in Ponorogo Regency is Agricultural Operational Cooperation (KOA). Factors such as land area, ANR fertilizer, organic fertilizer, and pesticides significantly influence rice production. However, seeds, liquid organic fertilizer, and labor do not significantly affect rice production. It is recommended that PT Ortani Mitra Sejahtera establish a clear partnership framework through transparent written contracts to minimize risks. Farmers are advised to focus on managing factors that significantly influence rice production, such as land area, ANR fertilizer, organic fertilizer, and pesticide use, while evaluating other factors such as seeds, liquid organic fertilizer, and labor to improve rice production.Keywords: partnership patterns, farming, rice.Â